Analisis Peran Konstitusi Dalam Menjamin Hak Asasi Manusia Dan Keadilan Sosial : Studi Kasus Negara Indonesia Dalam Konteks Dinamika Politik Kontemporer - Mustikasari, Febriani (Media Hukum Indonesia (MHI), 2024)
This research aims to analyze the role of the constitution in guaranteeing human rights and social justice in Indonesia, especially in the context of contemporary political dynamics. The constitution, as the highest basic law, has a vital role in regulating national and state life, including protecting the basic rights of citizens. The Indonesian case study shows how the constitution regulates mechanisms for protecting human rights and social justice amidst dynamic political change. Through a qualitative approach with document analysis and interviews, this research found that although the Indonesian constitution has established a strong legal framework to protect human rights and social justice, implementation in the field still faces various challenges. Factors such as political influence, corruption and economic inequality are the main obstacles to realizing true social justice. It is hoped that the results of this research can contribute to the development of more effective policies in strengthening the role of the constitution in guaranteeing human rights and social justice in Indonesia.